A Case Report on Ayurveda Management of Wet Eczema (Vicharchika) (International Journal of Ayurveda and Pharma Research, 2024)
Skin disorders are one of the major health issues in the present era. It is a multifaceted condition that includes the emotional and social impact on individuals, as it affects psychological status of person due to its appearance, severe itching, disturbs the daily routine. The prevalence of eczema is more common in rural areas than in urban ones. Eczema is an inflammatory reaction of the skin. Characterized by variable itching and soreness, crusting, dryness, erythema, excoriation, exudation, fissuring, hyper pigmentation, lichenification, oozing, scaling and vesiculation. No satisfactory treatment is available in contemporary medical practice except antihistamines and topical steroids. As it is a common chronic skin condition that can lead to recurrent infections and poor quality of life if left untreated. The clinical features can be correlated to Vicharchika in Ayurveda, as it is characterized by Kandu, Srava, Pidaka and Shyava varna. It has been described under Kshudra Kustas and it is a Rakta Pradoshaja Vikara, involving three Doshas with Kapha predominance. A case of 35 years male presenting with clinical features of diffuse hyperpigmented skin lesions all over the body (bilateral upper and lower limbs, abdomen, back, face and scalp) associated with severe itching and serous discharge since 2 months. The case was diagnosed as Sravi Vicharchika. Patients were treated on line of Rakta Pradoshaja Vikara (Kustha) i.e., Sroto sodhana and Dosha Shamana chikitsa was adopted, resulting in significant improvement in clinical features.